Dakwah dan Hukum Lingkungan - Acep Aripudin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2008)
The most important of Central isue in global era is global warning effect. One of its’causes is hyper-using of technology un-controlled, that become damage in this world. The other causes is un-controlled of exploitation to nature and is not be attend to ecosystem and environment live. Respons and reaction to global condition was spoken by a lot of people, –include – Islam, specially if looked according to Islamic law. Masalah-mursalah concept, as teoritic can be made basic in giving solution this global accident.